2016
DOI: 10.1007/s11302-015-9494-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia alters E-NTPDases, ecto-5′-nucleotidase, and ectosolic and cytosolic adenosine deaminase activities and expression from encephala of adult zebrafish (Danio rerio)

Abstract: Hyperglycemia is the main feature for the diagnosis of diabetes mellitus (DM). Some studies have demonstrated the relationship between DM and dysfunction on neurotransmission systems, such as the purinergic system. In this study, we evaluated the extracellular nucleotide hydrolysis and adenosine deamination activities from encephalic membranes of hyperglycemic zebrafish. A significant decrease in ATP, ADP, and AMP hydrolyses was observed at 111-mM glucose-treated group, which returned to normal levels after 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
(74 reference statements)
3
7
0
Order By: Relevance
“…The increase in the ATP concentration in the extracellular space depends on its release and/or its degradation rate, both mechanisms may operate concurrently. The increase in the basal ATP level and that induced by stimulation is an indication that the extracellular degradation of ATP/ADP was reduced, as was reported by Costa et al (2009) , in rat retinal cell cultures in high glucose, or in encephalic membranes from hyperglycemic zebrafish ( Capiotti et al, 2016 ). In addition, we infer that the diabetes-increased ATP released was similar to that reported in platelets from diabetic patients stimulated with thrombin ( Michno et al, 2007 ).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The increase in the ATP concentration in the extracellular space depends on its release and/or its degradation rate, both mechanisms may operate concurrently. The increase in the basal ATP level and that induced by stimulation is an indication that the extracellular degradation of ATP/ADP was reduced, as was reported by Costa et al (2009) , in rat retinal cell cultures in high glucose, or in encephalic membranes from hyperglycemic zebrafish ( Capiotti et al, 2016 ). In addition, we infer that the diabetes-increased ATP released was similar to that reported in platelets from diabetic patients stimulated with thrombin ( Michno et al, 2007 ).…”
Section: Discussionsupporting
confidence: 63%
“…(c) Reduced ADO metabolism by ADO deaminase also favors increased ADO levels. Encephalic membranes from hyperglycemic zebrafish exhibit a reduced expression of ADO deaminase ( Capiotti et al, 2016 ), a finding that could be relevant to the current results.…”
Section: Discussionsupporting
confidence: 60%
“…ADA hydrolyzes adenosine as a neuromodulator to inosine in a manner similar to ADAR catalyzing the water-free amino reaction on dsRNA substrates [35]. Some reports have shown that ADA plays a very important role in the transmission of adenosine signals from the central nervous system, the immune response to inflammation and the diagnosis of diseases in the humans and Drosophila melanogaster [22,36,37]. However, there are few reports on the ADA activity of ADAR.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of in vitro and mutant experimental evidence indicates that ADARs recognize the specific A site and deaminate through the secondary structure formed by the dsRNA substrate, and the precise location of the editing site in the substrate and the degree of editing are determined by the substrate itself [22,37,39]. Although the secondary structure is determined, until now it has not been possible to predict which A is the target site for ADAR editing based on the secondary structure of RNA.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is situated in the myoneural intersection and separates acetylcholine and different esters. Acetylcholinesterase alteration in diabetes can cause certain neurological maladies [7]. A similar convention was employed by Alvarez et al [1], who examined the impact of hyperglycaemia and its relation to retinopathy.…”
Section: Zebrafish As a Model To Studymetabolic Syndromementioning
confidence: 99%